Profil Saraf Nitrergik Sekum Ayam Pedaging yang Diinfeksi Eimeria tenella (THE PROFILE OF NEORAL NITRERGIC IN THE COECUM OF BROILER INFECTED WITH Emeria tenella) - Hana, Amelia; Astuti, Pudji; Fibrianto, Yuda Heru; ., Sarmin; Airin, Claude Mona (Jurnal Veteriner, 2016)
Neurotransmitter found in the enteric nervous system that plays an important role in a variety ofenteropathies, including inflammatory bowel disease. Alteration of nitrergic neurons has been reported to bedependent on the manner by which inflammation is caused. This study was performed to determine theprofile of neural nitrergic with Nicotinamide Adenine Dinucleotide Phosphate-diaphorase (NADPH-d)staining in the cecum of broiler infected by Eimeria tenella (E. tenella). Thirty six health free of coccidiosisbroiler one-day old chickens (DOC) used in this study. All of broiler adapted for 7 days with food and drinkgiven ad libitum then divided into three groups, each group consisted of 12 broilers. The 1st group wascontrol only given orally 1.0 ml of distilled water/ heads , while 2nd group was infected with a single dose of5x103 oocysts/ head orally, and 3rd group was infected with a single dose of 2x104 oocysts/ head orally. Onday 7 post infection, all of chickens were fasted for 12 hours then were euthanized and cecum was taken.Lesion score of cecum was assessed. Furthermore, tissue of the coecum was prepared for hisochemicalusing NADPH-d staining to determine morphology, and morhometric of nitrergic neurons. The resultshown that cecum lesion score of group I is 0, group II is +2, group III is +3. Neuron density in the cecum ofgroup I is 2794.96+4.65 neuron/cm2, group II is 4930.36+63.73 neuron/cm2 and group III is 7892.31+44.97 neuron/cm2. Neuron density of group II and III increased signifcantly (p<001) than group I. Nitrergic neurondesity of group III increased significantly (p<0.05) than that of group II. It was concluded that the infectionof E.tenella led to increase the number of neutrl mienteric nitrergic of the cecum. The higher lesion score ofcecum led to increase the number of mienteric nitrergic neuron.
Keywords: broiler chicken; coecum; Eimeria tenela; neural nitrergic